Synthesis and cytotoxic activities of azanaphthoquinone annelated pyrrolo hydrazone derivatives - Pongprom, Nipawan; Pungpo, Pornpan (Asia-Pacific Journal of Science and Technology, 2017)
We are interested in the synthesis of azanaphthoquinone annelated pyrrolo hydrazone derivatives as cytostatic compounds. The synthetic pathway was started from the commercially available 5-hydroxyisoquinoline by 3-steps reaction to obtain 1H-pyrrolo[3,2-g]isoquinoline-4,9-dione. N-Alkylation of nitrogen atom in pyrrole ring was carried out under basic conditions with different side chains to obtain mono-substituted azanaphthoquinone annelated pyrroles with 2 to 4-carbon side chains in moderate to good yields. The hydrazone derivatives were synthesized by condensation reaction of mono-substituted products 5 with hydrazine under basic conditions. The reactions occurred regioselectively at C-4 to give products 6. The synthesized compounds were purifi ed by column chromatography and characterized by spectroscopic techniques including 1H NMR, 13C NMR, IR, UV and LC-MS. The antiproliferative activity of the synthesized compounds was evaluated on cervical carcinoma: KB/HeLa by using xCELLigence from Roche. The results show that the mono-substituted products with 2-carbon side chain (5b) exhibited a very good activity with IC50 value of 0.008 μM. The hydrazone 6a showed higher inhibitory activity with IC50 value of 0.282 μM compared to the mono-substituted derivative 5a. The side chains with cyclic amine are of interest for the further studies.